Sympatric morphotypes of the restricted-range Tashan Cave Garra: distinct species or a case of phenotypic plasticity? - Hashemzadeh Segherloo, Iraj; Najafi Chaloshtory, Sajad; Naser, Murtada D.; Yasser, Amaal Gh; Tabatabaei, Seyedeh Narjes; Piette-Lauziere, Gabriel; Mashtizadeh, Amirhossein; Elmi, Amirmohammad; Sedighi, Omid; Changizi, Alieh; Hallerman, Eric; Bernatchez, Louis (Environmental biology of fishes, 2022)
Among Tashan cave barb Garra tashanensis inhabiting a small cave in southwest Iran, two mental disc (sucking mouth disc) forms were observed. To assess their phylogenetic relationships, disc-less and disc-bearing individuals were analyzed using mitochondrial cytochrome oxidase subunit I ( COI ) partial DNA sequences. Both mental disc forms nested within one clade with absolute bootstrap support ( BS = 100), and the genetic distances between the disc-bearing and disc-less individuals (0.3–0.8%) were considerably lower than inter-species mtDNA sequence distances reported among members of the genus Garra ; further, most species delimitation algorithms used here showed disc-bearing and disc-less Tashan cave barbs to be members of a single taxonomic unit. Hence, the observed mental disc variation was not inferred to be a taxonomic feature or a consequence of character displacement. Instead, it was inferred to be a case of character release to diversify among ecological niches in the limited subterranean habitat or a case of relaxed selection, which should be clarified in detail in follow-up ecological and population genetic studies.